AIRCC-Clim: A user-friendly tool for generating regional probabilistic climate change scenarios and risk measures. (November 2022) - Estrada, Francisco; Calderón-Bustamante, Oscar; Botzen, Wouter; Velasco, Julián A.; Tol, Richard S.J.
Abstract: Complex physical models are the most advanced tools available for producing realistic simulations of the climate system. However, such levels of realism imply high computational cost and restrictions on their use for policymaking and risk assessment. Two central characteristics of climate change are uncertainty and that it is a dynamic problem in which international actions can significantly alter climate projections and information needs, including partial and full compliance of global climate goals. Here we present AIRCC-Clim, a simple climate model emulator that produces regional probabilistic climate change projections of monthly and annual temperature and precipitation, as well as risk measures, based both on standard and user-defined emissions scenarios for six greenhouse gases. AIRCC-Clim emulates 37 atm-ocean coupled general circulation models with low computational and technical requirements for the user. This standalone, user-friendly software is designed for a variety of applications including impact assessments, climate policy evaluation and integrated assessment modelling. Highlights: A new tool for generating probabilistic regional climate change scenarios and risk measures AIRCC-Clim is a standalone, user-friendly software designed for a variety of applications including impact, vulnerability and adaptation assessments, integrated assessment modelling, It includes a graphical interface that allows the quick evaluation of the consequences on global and regional climate of user-defined experiments of international mitigation policies.